Teamwork and clinician burnout in Swiss intensive care: the predictive role of workload, and demographic and unit characteristics (Swiss Medical Weekly, 2019)
AIM The levels of teamwork and clinician burnout in healthcare differ depending on demographic and unit characteristics. However, the impact of these characteristics varies between clinical settings. In addition, the impact of objectively measured workload in such settings is largely unknown. The aim of this study was to analyse the predictive role of demographic (e.g., professional experience) and unit (e.g., unit size) characteristics, and workload (e.g., nursing interventions) in explaining teamwork and clinician burnout in Swiss intensive care units (ICUs). METHODS This was as cross-sectional multi-source study. Participants were 1148 nurses and 243 physicians working in 55 ICUs. They provided demographic information and answered a questionnaire on teamwork and clinician burnout. In addition, unit characteristics and surrogate measures of workload were extracted from a central database that accumulates patient and unit data routinely collected by the ICUs. We conducted multilevel regression analyses to detect relationships between study variables. RESULTS Clinicians who worked predominantly dayshifts reported better teamwork and lower burnout. Physicians and clinicians in leadership positions also reported better teamwork. Clinicians in leadership positions furthermore reported higher personal accomplishment, whereas clinicians in training reported higher emotional exhaustion. Of the unit characteristics, workload was positively associated with self-reported burnout. Clinicians working in medical and surgical ICUs (compared with interdisciplinary and paediatric ICUs) reported higher emotional exhaustion. Clinicians working in university hospitals and in surgical/medical ICUs reported lower teamwork quality and higher burnout. CONCLUSION We identified several demographic and unit-based factors in Swiss ICUs that were associated with lower perceptions of the quality of teamwork and higher self-reported burnout. Discrepant experiences regarding the quality of teamwork based on professional role, professional status and experience might affect team effectiveness. Furthermore, this study showed the importance of workload management, as objectively measured workload was associated with higher self-reported burnout. Results suggested that certain clinician groups (e.g., working predominantly night shifts) were at higher risk for burnout, thus highlighting the importance of providing additional support to these groups. Lastly, special attention should be paid to medical and surgical ICUs, which reported the highest level of burnout. Because this is a cross-sectional study, no conclusions can be drawn regarding causal relationships.